2022
DOI: 10.1155/2022/5325431
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Liver Fibrosis and Its TCM Therapeutic Perspectives

Abstract: Liver fibrosis is a pathological process of abnormal tissue proliferation in the liver caused by various pathogenic factors, which will further develop into cirrhosis or even hepatocellular carcinoma if liver injury is not intervened in time. As a diffuse progressive liver disease, its clinical manifestations are mostly excessive deposition of collagen-rich extracellular matrix resulting in scar formation due to liver injury. Hepatic fibrosis can be caused by hepatitis B and C, fatty liver, alcohol, and rare d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 150 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…The balance of ECM is regulated by matrix metalloproteinases (MMP) and tissue inhibitor of metalloproteinases (TIMP). 3,4 The increase of autophagy can accelerate the metabolism of lipid droplets (LDs) in aHSC, which provides the energy for the activation of HSC and lead to liver fibrosis. [5][6][7] However, the autophagy in different liver cells has completely opposite effects on liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The balance of ECM is regulated by matrix metalloproteinases (MMP) and tissue inhibitor of metalloproteinases (TIMP). 3,4 The increase of autophagy can accelerate the metabolism of lipid droplets (LDs) in aHSC, which provides the energy for the activation of HSC and lead to liver fibrosis. [5][6][7] However, the autophagy in different liver cells has completely opposite effects on liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…It also exerts hepatoprotective effects by inhibiting the autophagy of hepatocytes and increasing apoptosis [ 14 ] . Nan et al [ 15 ] and Yang et al [ 16 ] have reported that isorhamnetin could weaken CCl4-induced hepatic fibrosis by reducing TGF-β mediated Smad signaling. However, it is unclear whether isorhamnetin can reduce hepatic fibrosis in the PDGF-BB-induced HSC-T6.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical application of dialectical principles is fundamental to TCM therapy. According to studies, TCM is an effective way to halt cirrhosis progression and improve prognosis (Dong et al, 2015;Nan et al, 2022). TCM treatment of hepatitis B cirrhosis has gradually become a new trend.…”
Section: Introductionmentioning
confidence: 99%